Small business revolution : how owners and entrepreneurs can succeed - McCarthy, Barry C. (Wiley, 2022)
"Part uplifting narrative and part instructional manual, Small Business Revolution explains how SMBs can endure a recession and remake themselves for a post-pandemic marketplace. Using examples from the award-winning TV show of the same name and from Deluxe's 4.5 million customers, entrepreneurs and small business owners will learn how to manage cash flow in a recession, navigate payroll costs in a turbulent time, adjust to new customer buying experiences, embrace new revenue and marketing channels, and engage and leverage their community to build back stronger than ever"--